Islet-1 Overexpression in Human Mesenchymal Stem Cells Promotes Vascularization Through Monocyte Chemoattractant Protein-3. (17th June 2014) - Liu, Jia; Li, Weiqiang; Wang, Yinfen; Fan, Wendong; Li, Panlong; Lin, Wanyi; Yang, Daya; Fang, Rong; Feng, Mingzhe; Hu, Chengheng; Du, Zhimin; Wu, Guifu; et al.
Abstract : The LIM-homeobox transcription factor islet-1 (ISL1) has been proposed to mark a cardiovascular progenitor cell lineage that gives rise to cardiomyocytes, endothelial cells, and smooth muscle cells. The aim of this study was to investigate whether forced expression of ISL1 in human mesenchymal stem cells (hMSCs) influenced the differentiation capacity and angiogenic properties of hMSCs. The lentiviral vector, EF1α-ISL1, was constructed using the Multisite Gateway System and used to transduce hMSCs. We found that ISL1 overexpression did not alter the proliferation, migration, or survival of hMSCs or affect their ability to differentiate into osteoblasts, adipocytes, cardiomyocytes, or endotheliocytes. However, ISL1-hMSCs differentiated into smooth muscle cells more efficiently than control hMSCs. Furthermore, conditioned medium from ISL1-hMSCs greatly enhanced the survival, migration, and tube-formation ability of human umbilical vein endothelial cells (HUVECs) in vitro. In vivo angiogenesis assays also showed much more vascular-like structures in the group cotransplanted with ISL1-hMSCs and HUVECs than in the group cotransplanted with control hMSCs and HUVECs. Quantitative RT-PCR and antibody arrays detected monocyte chemoattractant protein-3 (MCP3) at a higher level in conditioned medium from ISL1-hMSCs cultures than in conditioned medium from control hMSCs. Neutralization assays showed that addition of an anti-MCP3 antibody to ISL1-hMSCs-conditioned medium efficiently abolished the angiogenesis-promoting effect of ISL1-hMSCs. Our data suggest that overexpression of ISL1 in hMSCs promotes angiogenesis in vitro and in vivo through increasing secretion of paracrine factors, smooth muscle differentiation ability, and enhancing the survival of HUVECs. Stem Cells   2014;32:1843–1854